Lexical richness of newspaper editorials published in Southeast Asian countries - Dwi Indarti (Universitas Syiah Kuala, 2020)
This paper investigates the lexical richness of newspaper editorials written by the writers from ESL (English as a Second Language) and EFL (English as a Foreign Language) of Southeast Asian countries. Using editorial texts published on the same day in two major online newspapers from Malaysia and the Philippines as representative of ESL countries, and two major online newspapers published in Indonesia and Thailand that represent EFL countries, this paper compares the production of Type Token Ratio (TTR) as a measurement of the lexical richness. This study displays a profile of lexical richness gained by submitting the texts into a vocabulary profiler program namely Lexical Frequency Profile (LFP) proposed by Laufer and Nation (1995) to highlight the emergence of the high-frequency word list (K1 and K2 words) and low-frequency word list (AWL and Off-list words). In general, the results show that in all terms of word lists, ESL texts have more varied vocabulary than EFL texts as indicated by the TTR scores (ESL: 0.51; EFL: 0.49). Although the gap of the TTR scores between ESL and EFL texts is slightly insignificant, a bigger TTR score indicates a high lexical richness, while a smaller TTR score shows a low lexical richness. The higher score of TTR in ESL texts could be understood since English plays an important role in education, governance policy and popular culture in those countries (i.e. Malaysia and the Philippines), meanwhile, in Indonesia and Thailand, it plays a lesser role.